THE METHODS OF STUDYING LEGAL LANGUAGE IN VIEW OF THE ONTOLOGICAL NATURE OF LAW - LIZISOWA, Maria Teresa (Comparative Legilinguistics, 2013)
The article is dedicated to methodology of studying the language of legislature in a theoretical aspect. The author proposes interdisciplinary studies of legal language, with regard to ontological nature of law in the concept of natural law and assumes that natural law serves a validative function vis-à-vis positive law. She believes that law, understood as phenomenon which comes down to linguistic objects, becomes identical with legal texts (Lat. lex), whereas law understood as a relationship between man and object in the aspect of obligation and duty (Lat. debitum) equals the rights (Lat. ius), while both the terms refer to the same phenomenon presented in substantial approach as well as well existential. The article includes a survey of legal and linguistic studies of language of communication with the field of law, and puts forward some aspects of presenting the theory of legal language. In the study of legal language theory the author proposes methodological eclecticism, as a result of multi-aspect ontological status of law, linguistic status of legal language and specific relationship between legal language structures and legal reality structures. She claims that research carried out to date within the fields of philosophy, theory of law and linguistics, brings about the possibilities for integrative study of the levels of legal language – i. e. semantic, syntactic and pragmatic – that would allow to characterise legal language as a register of ethnic language presented a systems approach. The author also states that the theory of legal language could be studied only in the context of legal language, used by professional lawyers who deal with legal practice and legal education, as well as in opposition to the other object languages, from which legal language takes its linguistic forms to communicate the content belonging to various fields of legal regulations, as well as in opposition to general language which constitutes the ethnic basis of legal language. The research approach, according to the author, should be open to the up to date achievements of philosophers, lawyers and linguists.